Lake water and sediment chemistry responses to reductions in mercury, other heavy metals, and sulfur dioxide emissions from the Flin Flon smelter, Manitoba, Canada, with historic comparisons to other emitters - Marlene S. Evans; Jane L. Kirk; Johan A. Wiklund; Kristin J. Painter; John P. Smol; Kathleen M. Rühland; Sarah L. Roberts; Brigitte S.G. Simmatis; Derek C.G. Muir (Science of The Total Environment, 2026)

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

Reply to Beltaos (2024). Letter to the Editor regarding “Paleofloodscapes: Application of sediment source fingerprinting to track flood regime change over space and time at the Peace-Athabasca Delta, Canada” by Kay et al. (2024), Sci. Total Environ. 912 169538 - Mitchell L. Kay; Lauren A. MacDonald; Johan A. Wiklund; Cory A.M. Girard; Brent B. Wolfe; Roland I. Hall (Science of The Total Environment, 2024)

A new species of Erinaceusyllis (Annelida: Syllidae) discovered at a wood-fall in the eastern Clarion-Clipperton zone, central Pacific ocean - Christian L. Nilsson; Helena Wiklund; Adrian G. Glover; Guadalupe Bribiesca-Contreras; Thomas G. Dahlgren (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

P19-03 Integration of transcriptomics data for ED assessments using an Adverse Outcome Pathway Network approach - L. Wiklund; E. Vincent; A. Beronius (Toxicology Letters, 2024)

‘Paleofloodscapes’: Application of sediment source fingerprinting to track flood regime change over space and time at the Peace-Athabasca Delta, Canada - Mitchell L. Kay; Lauren A. MacDonald; Johan A. Wiklund; Cory A.M. Girard; Brent B. Wolfe; Roland I. Hall (Science of The Total Environment, 2024)

High-density linkage maps and chromosome level genome assemblies unveil direction and frequency of extensive structural rearrangements in wood white butterflies (Leptidea spp.) - L. Höök; K. Näsvall; R. Vila; C. Wiklund; N. Backström (Chromosome Research, 2023)
Karyotypes are generally conserved between closely related species and large chromosome rearrangements typically have negative fitness consequences in heterozygotes, potentially driving speciation. In the order Lepidoptera, most investigated species have the ancestral karyotype and gene synteny is often conserved across deep divergence, although examples of extensive genome reshuffling have recently been demonstrated. The genus Leptidea has an unusual level of chromosome variation and rearranged sex chromosomes, but the extent of restructuring across the rest of the genome is so far unknown. To explore the genomes of the wood white ( Leptidea ) species complex, we generated eight genome assemblies using a combination of 10X linked reads and HiC data, and improved them using linkage maps for two populations of the common wood white ( L. sinapis ) with distinct karyotypes. Synteny analysis revealed an extensive amount of rearrangements, both compared to the ancestral karyotype and between the Leptidea species, where only one of the three Z chromosomes was conserved across all comparisons. Most restructuring was explained by fissions and fusions, while translocations appear relatively rare. We further detected several examples of segregating rearrangement polymorphisms supporting a highly dynamic genome evolution in this clade. Fusion breakpoints were enriched for LINEs and LTR elements, which suggests that ectopic recombination might be an important driver in the formation of new chromosomes. Our results show that chromosome count alone may conceal the extent of genome restructuring and we propose that the amount of genome evolution in Lepidoptera might still be underestimated due to lack of taxonomic sampling.

Paleolimnological evaluation of metal(loid) enrichment from oil sands and gold mining operations in northwestern Canada - Mitchell L. Kay; Izabela Jasiak; Wynona H. Klemt; Johan A. Wiklund; Jelle A. Faber; Lauren A. MacDonald; James V.K. Telford; Cory A.M. Savage; Colin A. Cooke; Brent B. Wolfe; Roland I. Hall (Environmental Research, 2023)

Reversible mutations in gliding motility and virulence genes: A flexible and efficient phage defence mechanism in Flavobacterium psychrophilum - Jóhanna Jørgensen; Krister Sundell; Daniel Castillo; Liv S. Dramshøj; Natasja B. Jørgensen; Susie B. Madsen; Lotta Landor; Tom Wiklund; Valentina L. Donati; Lone Madsen; Inger Dalsgaard; Mathias Middelboe (Environmental Microbiology, 2022)
Flavobacteria are among the most important pathogens in freshwater salmonid aquaculture worldwide. Due to concerns regarding development of antibiotic resistance, phage therapy has been proposed as a solution to decrease pathogen load. However, application of phages is challenged by the development of phage resistance, and knowledge of the mechanisms and implications of phage resistance is therefore required. To study this, 27 phage‐resistant isolates of F. psychrophilum were genome sequenced and characterized to identify genetic modifications and evaluate changes in phenotypic traits, including virulence against rainbow trout. Phage‐resistant isolates showed reduction or loss of gliding motility, proteolytic activity, and adhesion to surfaces, and most isolates were completely non‐virulent against rainbow trout fry. Genomic analysis revealed that most phage‐resistant isolates had mutations in genes associated with gliding motility and virulence. Reversal of these mutations in a sub‐set of isolates led to regained motility, proteolytic activity, virulence and phage susceptibility. Although costly, the fast generation of phage resistance driven by single, reversible mutations likely represents a flexible and efficient phage defence mechanism in F. psychrophilum . The results further suggest that phage administration in aquaculture systems to prevent F. psychrophilum outbreaks selects for non‐virulent phage‐resistant phenotypes.

Interactive effects of aging and aerobic capacity on energy metabolism–related metabolites of serum, skeletal muscle, and white adipose tissue - Haihui Zhuang; Sira Karvinen; Timo Törmäkangas; Xiaobo Zhang; Xiaowei Ojanen; Vidya Velagapudi; Markku Alen; Steven L. Britton; Lauren G. Koch; Heikki Kainulainen; Sulin Cheng; Petri Wiklund (GeroScience, 2021)
Aerobic capacity is a strong predictor of longevity. With aging, aerobic capacity decreases concomitantly with changes in whole body metabolism leading to increased disease risk. To address the role of aerobic capacity, aging, and their interaction on metabolism, we utilized rat models selectively bred for low and high intrinsic aerobic capacity (LCRs/HCRs) and compared the metabolomics of serum, muscle, and white adipose tissue (WAT) at two time points: Young rats were sacrificed at 9 months of age, and old rats were sacrificed at 21 months of age. Targeted and semi-quantitative metabolomics analysis was performed on the ultra-pressure liquid chromatography tandem mass spectrometry (UPLC-MS) platform. The effects of aerobic capacity, aging, and their interaction were studied via regression analysis. Our results showed that high aerobic capacity is associated with an accumulation of isovalerylcarnitine in muscle and serum at rest, which is likely due to more efficient leucine catabolism in muscle. With aging, several amino acids were downregulated in muscle, indicating more efficient amino acid metabolism, whereas in WAT less efficient amino acid metabolism and decreased mitochondrial β-oxidation were observed. Our results further revealed that high aerobic capacity and aging interactively affect lipid metabolism in muscle and WAT, possibly combating unfavorable aging-related changes in whole body metabolism. Our results highlight the significant role of WAT metabolism for healthy aging.

Building upon open-barrel corer and sectioning systems to foster the continuing legacy of John Glew - James V. Telford; Mitchell L. Kay; Harman Vander Heide; Johan A. Wiklund; Tanner J. Owca; Jelle A. Faber; Brent B. Wolfe; Roland I. Hall (Journal of Paleolimnology, 2021)

Use of pre-industrial baselines to monitor anthropogenic enrichment of metals concentrations in recently deposited sediment of floodplain lakes in the Peace-Athabasca Delta (Alberta, Canada) - Tanner J. Owca; Mitchell L. Kay; Jelle Faber; Casey R. Remmer; Nelson Zabel; Johan A. Wiklund; Brent B. Wolfe; Roland I. Hall (Environmental Monitoring and Assessment, 2020)
Well-designed monitoring approaches are needed to assess effects of industrial development on downstream aquatic environments and guide environmental stewardship. Here, we develop and apply a monitoring approach to detect potential enrichment of metals concentrations in surficial lake sediments of the Peace-Athabasca Delta (PAD), northern Alberta, Canada. Since the ecological integrity of the PAD is strongly tied to river floodwaters that replenish lakes in the delta, and the PAD is located downstream of the Alberta oil sands, concerns have been raised over the potential transport of industry-supplied metals to the PAD via the Athabasca River. Surface sediment samples were collected in September 2017 from 61 lakes across the delta, and again in July 2018 from 20 of the same lakes that had received river floodwaters 2 months earlier, to provide snapshots of metals concentrations (Be, Cd, Cr, Cu, Ni, Pb, V, and Zn) that have recently accumulated in these lakes. To assess for anthropogenic enrichment, surficial sediment metals concentrations were normalized to aluminum and compared to pre-industrial baseline (i.e., reference) metal-aluminum linear relations for the Athabasca and Peace sectors of the PAD developed from pre-1920 measurements in lake sediment cores. Numerical analysis demonstrates no marked enrichment of these metals concentrations above pre-1920 baselines despite strong ability (> 99% power) to detect enrichment of 10%. Measurements of river sediment collected by the Regional Aquatics- and Oil Sands-Monitoring Programs (RAMP/OSM) also did not exceed pre-1920 concentrations. Thus, results presented here show no evidence of substantial oil sands-derived metals enrichment of sediment supplied by the Athabasca River to lakes in the PAD and demonstrate the usefulness of these methods as a monitoring framework.

Effects of shoreline permafrost thaw on nutrient dynamics and diatom ecology in a subarctic tundra pond - M. Q. Morison; O. Volik; R. I. Hall; J. A. Wiklund; M. L. Macrae; R. M. Petrone (Journal of Paleolimnology, 2019)

Implications of population connectivity studies for the design of marine protected areas in the deep sea: An example of a demosponge from the Clarion‐Clipperton Zone - Sergi Taboada; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Vasiliki Koutsouveli; Nadiezhda Santodomingo; Andrew C. Dale; Craig R. Smith; Daniel O. B. Jones; Thomas G. Dahlgren; Adrian G. Glover (Molecular Ecology, 2018)
The abyssal demosponge Plenaster craigi inhabits the Clarion‐Clipperton Zone ( CCZ ) in the northeast Pacific, a region with abundant seafloor polymetallic nodules with potential mining interest. Since P. craigi is a very abundant encrusting sponge on nodules, understanding its genetic diversity and connectivity could provide important insights into extinction risks and design of marine protected areas. Our main aim was to assess the effectiveness of the Area of Particular Environmental Interest 6 ( APEI ‐6) as a potential genetic reservoir for three adjacent mining exploration contract areas ( UK ‐1A, UK ‐1B and OMS ‐1A). As in many other sponges, COI showed extremely low variability even for samples ~900 km apart. Conversely, the 168 individuals of P. craigi, genotyped for 11 microsatellite markers, provided strong genetic structure at large geographical scales not explained by isolation by distance (IBD). Interestingly, we detected molecular affinities between samples from APEI ‐6 and UK ‐1A, despite being separated ~800 km. Although our migration analysis inferred very little progeny dispersal of individuals between areas, the major differentiation of OMS ‐1A from the other areas might be explained by the occurrence of predominantly northeasterly transport predicted by the HYCOM hydrodynamic model. Our study suggests that although APEI ‐6 does serve a conservation role, with species connectivity to the exploration areas, it is on its own inadequate as a propagule source for P. craigi for the entire eastern portion of the CCZ . Our new data suggest that an APEI located to the east and/or the south of the UK ‐1, OMS ‐1, BGR , TOML and NORI areas would be highly valuable.

Mitochondrial genome and polymorphic microsatellite markers from the abyssal sponge Plenaster craigi Lim & Wiklund, 2017: tools for understanding the impact of deep-sea mining - Sergi Taboada; Nathan J. Kenny; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Thomas G. Dahlgren; Adrian G. Glover (Marine Biodiversity, 2018)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Genetic variants of TNFSF4 and risk for carotid artery disease and stroke - P. S. Olofsson; L. Å. Söderström; C. Jern; A. Sirsjö; M. Ria; E. Sundler; U. de Faire; P. G. Wiklund; J. Öhrvik; U. Hedin; G. Paulsson-Berne; A. Hamsten; et al. (Journal of Molecular Medicine, 2009)

Flavobacterium psychrophilum associated with mortality of farmed perch, Perca fluviatilis L. - L‐G Lönnström; M L Hoffrén; T Wiklund (Journal of Fish Diseases, 2008)

Efficacy of injection vaccines against Flavobacterium psychrophilum in rainbow trout, Oncorhynchus mykiss (Walbaum) - J Madetoja; L‐G Lönnström; C Björkblom; G Uluköy; G Bylund; C Syvertsen; K Gravningen; E‐A Norderhus; T Wiklund (Journal of Fish Diseases, 2006)
Efficacy of mineral oil‐based experimental injection vaccines against Flavobacterium psychrophilum were tested in rainbow trout, Oncorhynchus mykiss (Walbaum), under laboratory and field conditions. The vaccines consisted of formalin‐ or heat‐inactivated whole bacterium cell preparations of two different serotypes (Fd and Th) or a combination of serologically different F. psychrophilum (Fd and/or Th and/or Fp T ;Th). Specific antibody responses against the bacterium in plasma and skin mucus were evaluated post‐vaccination with enzyme‐linked immunosorbent assay. Efficacy of the vaccinations was determined by challenge trials to F. psychrophilum with the vaccinated rainbow trout. Significantly higher antibody levels in plasma were detected in vaccinated fish compared with mock‐vaccinated fish. Injection vaccination did not trigger specific antibody production in the skin mucus. Significantly higher survival of i.p. vaccinated fish compared with non‐vaccinated fish was observed during the challenge. The results suggest that mineral oil‐based injectable vaccines containing formalin‐ or heat‐inactivated virulent cells of F. psychrophilum effectively triggered specific antibody production and protected the fish against bacterial cold water disease.

Phenotypic and genotypic characterization of Flavobacterium psychrophilum from Finnish fish farms - J Madetoja; M‐L Hänninen; V Hirvelä–Koski; I Dalsgaard; T Wiklund (Journal of Fish Diseases, 2001)
Finnish isolates ( n =37) of Flavobacterium psychrophilum isolated from farmed salmonids were studied using phenotypic and genotypic characteristics. The characteristics of isolates were compared with the characteristics of Swedish and Estonian F. psychrophilum isolates and the type strain, F. psychrophilum NCIMB 1947 T . Multiple isolates from eight disease outbreaks were examined to determine differences between isolates from a single outbreak. The F. psychrophilum isolates represented a biochemically homogeneous group. However, some minor differences in biochemical and physiological characteristics were observed. Seven different antigenic patterns among Finnish isolates were detected and the results suggest a new serotype of F. psychrophilum . Using Cla Ι, Hae ΙΙΙ and Pvu ΙΙ restriction enzymes in ribotyping analyses 13 different genotypes were demonstrated and a possible relationship between serotype Fd and genotype F1 was determined. There were no significant differences between the isolates from Finland, Estonia, Sweden and the type strain of F. psychrophilum .

Intracellular hepatitis C virus RNA-dependent RNA polymerase activity - L. Goobar-Larsson; L. Wiklund; S. Schwartz (Archives of Virology, 2001)

Mass and production rate of ejaculates in relation to monandry/polyandry in butterflies - L. Svrd; C. Wiklund (Behavioral Ecology and Sociobiology, 1989)

Fecundity, egg weight and longevity in relation to multiple matings in females of the monarch butterfly - L. Svrd; C. Wiklund (Behavioral Ecology and Sociobiology, 1988)